Mitral Valve Surgery for Rheumatic Lesions in Young Patients. (May 2016) - Cardoso, B.; Loureiro, P.; Gomes, I.; Gordo, A.; Banazol, N.; Fragata, I.; Trigo, C.; Pinto, F.; Fragata, José
Background: The appropriateness of rheumatic mitral valve repair remains controversial due to the risks of recurrent mitral dysfunction and need for reoperation. The aims of this study were to determine the overall short- and long-term outcomes of pediatric rheumatic mitral valve surgery in our center. Methods: Single-center, observational, retrospective study that analyzed the results of rheumatic mitral valve surgery in young patients, consecutively operated by the same team, between 1999 and 2014. Results: We included 116 patients (mean age = 12.6 ± 3.5 years), of which 66 (57%) were females. A total of 116 primary surgical interventions and 22 reoperations were performed. Primary valve repair was possible in 86 (74%) patients and valve replacement occurred in 30 (26%). Sixty percent of the patients were followed up beyond three months after surgery (median follow-up time = 9.2 months [minimum = 10 days; maximum = 15 years]). Long-term clinical outcomes were favorable, with most patients in New York Heart Association functional class I (89.6%) and in sinus rhythm (85%). Freedom from reoperation for primary valve repair at six months, five years, and ten years was 96.4% ± 0.25%, 72% ± 0.72%, and 44.7% ± 1.34%, respectively. Freedom from reoperation for primary valve replacement at six months, five years, and ten years was 100%, 91.7% ± 0.86%, and 91.7% ± 0.86%, respectively. Mitral stenosis as the primary lesion dictated early reintervention. Conclusions: Despite the greater rate of reoperation, especially when the primary lesion was mitral stenosis, rheumatic mitral valve repair provides similar clinical outcomes as compared with replacement, with the advantage of avoiding anticoagulation.